Primary combustion control of cocoa pod husk pellets: Effects of kaolin additives and air velocity on efficiency and emissions - Rincon-Quintero, A D; Ardila-Caballero, Zirley; Sandoval Rodriguez, Camilo Leonardo; Almanza Merchán, Pedro José; Fernandez Fernandez, Edilma (Sustainable Engineering and Innovation, 2025)
The control of primary combustion methods directly influences thermal efficiency and atmospheric emission concentrations. In this context, the objective of the present study was to evaluate the impact of the type of biofuel through the incorporation of additives, as well as the operating conditions of the equipment by regulating the oxidizing agent velocity. For this purpose, a densified biomass (pellet) burner was employed, equipped with a thermal storage tank, a centrifugal fan for supplying the oxidizing agent, and a feeding system based on a screw conveyor with ON/OFF control. Emission characterization (CO, CO?, O?, and H?S) was conducted using a gas analyzer, while equipment efficiency was determined from the calculation of the experimental lower heating value (LHV) obtained from four (4) test runs. The results demonstrated that the addition of additives in the production of cocoa pod husk (CPH) pellets improved the compaction, durability, and structural stability of the biofuel, which led to more complete combustion. In particular, the use of kaolin, combined with an airflow velocity range between 5.0 and 6.5 m/s, provided the best system performance by enabling faster ignition, complete biofuel consumption, and an increase in bottom ash due to particle agglomeration. In conclusion, the incorporation of additives and the controlled adjustment of airflow velocity optimize the efficiency of the combustion process, while simultaneously reducing fly ash entrainment and lowering atmospheric emission concentrations.